(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
Nowadays it is major to use recognition systems in each aspects of human life to automate and to speed up some processes where we need quickly find something. This article examines the main trend of technologies and algorithms of recognition systems which can use now and can give good results. The disadvantages and advantages of three common schemes for the implementation of the face recognition system are provided. The coefficients such as FAR and FRR are calculated for the main methods of biometric identification. The dynamics of the development of the use of face recognition systems is described. It is known that knowledge of trends and dynamics of the development are very important and first main step in research process. Of course, without knowing what is required and changing in this area, it is difficult to judge what exactly is in demand right now. It will also be impossible without knowledge to predict or make assumptions about what will be in demand in the future.